(untitled) (Marketing Journal, 2026)
Abstract The study analyzed factors and strategic directions for increasing investment attractiveness in the national economy. Macroeconomic stability, institutional quality, infrastructure development, human capital level, and innovation potential were assessed as key components shaping the investment environment. The analysis was conducted using Dunning’s OLI paradigm and Porter’s competitiveness theory. Data from UNCTAD, the World Bank, the IMF, and national statistics were used to examine the dynamics of investment activity in Uzbekistan. The results showed that improvement of the legal environment, acceleration of digital transformation, development of cluster policy, and application of tax incentives significantly influenced the expansion of investment flows. The research formulated scientific conclusions aimed at strengthening the investment potential of the national economy. Keywords: investment attractiveness, OLI paradigm, institutional environment, human capital, digital transformation, cluster policy, national economy, strategic management, FDI.